Information sharing and data protection in the area of freedom, security and justice : towards harmonised data protection principles for information exchange at EU-level - Boehm, Franziska (Springer, 2012)
Developments in EU internal security policy, such as increased information sharing and the access of EU agencies, in particular Europol and Eurojust, to data stored in European information systems raise interesting questions regarding the balance between the rights of individuals and security interests. This book deals with this topic